Spotlight on ORNAC Members - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2018)
Leonor De Biasio completed her Nursing Diploma Program at Humber College in 1995. She received her Bachelor of Science Degree in Nursing in 2005, from Ryerson University, and in the same year successfully obtained CNA Certiﬁcation in the perioperative specialty Leonor completed the Operating Room Post-Graduate Nursing Program, at George Brown College, in 1996. She is currently pursuing her Master of Education specializing in Educational Leadership.